2021
DOI: 10.1155/2021/2741271
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Adult Sepsis Patients in the Intensive Care Units in a Tertiary Hospital in Jordan: An Observational Study

Abstract: Sepsis is a global health issue that is commonly encountered in the intensive care unit (ICU) and is associated with high morbidity and mortality. Available data regarding sepsis in low- and middle-income countries (LMIC) is lacking compared to higher income countries, especially using updated sepsis definitions. The lack of recent data on sepsis in Jordan prompted us to investigate the burden of sepsis among Jordanian ICU patients. We conducted a prospective cohort study at Jordan University Hospital, a terti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…According to the Agency for Health Care Research and Quality, the average hospital stay is 4.5 days worldwide [ 47 ]. However, previous Jordanian studies show that the LoS is much higher [ 13 , 48 , 49 ]. In the present study findings, the mean length of ICU and hospital stay was high compared to some studies [ 50 , 51 ] and low compared to other studies [ 43 , 52 ].…”
Section: Discussionmentioning
confidence: 93%
“…According to the Agency for Health Care Research and Quality, the average hospital stay is 4.5 days worldwide [ 47 ]. However, previous Jordanian studies show that the LoS is much higher [ 13 , 48 , 49 ]. In the present study findings, the mean length of ICU and hospital stay was high compared to some studies [ 50 , 51 ] and low compared to other studies [ 43 , 52 ].…”
Section: Discussionmentioning
confidence: 93%
“… 9 An observational previous study showed diabetes as the most prevalent comorbidities, which is 47.9%. 9 In our study, hypertension was the most common comorbidity followed by diabetes mellitus and COPD. A similar finding was present in a study conducted in India.…”
Section: Discussionmentioning
confidence: 98%
“…A previous observational study showed that the mortality rate of patients with sepsis was 57.80% while another descriptive observational study in India showed a mortality rate of 42.2%. 9 Out of 278 patients, 87 (31.29%) were discharged normally and 60 (21.58%) died during their hospital stay. In a previous study, the mortality rate was 36.5%, a similar study showed 35.2% and 39.3% mortality.…”
Section: Discussionmentioning
confidence: 99%
“… 4 In a Colombian city, the prevalence was found to be 44%, 6 and in Jordan, it was 23.3%. 7 The differences in the prevalence were due to differences in setting, differences in the diagnostic criteria used and population.…”
Section: Discussionmentioning
confidence: 99%